A Life Cycle Assessment of Disposable Medical Masks and its Impacts Towards the Environment in the Context of the COVID-19 Pandemic - Batungbacal, Marielle A. (Animo Repository, 2021)
This study is about the Life Cycle Assessment of Disposable Medical Masks and its Environmental Impacts in the context of the COVID-19 pandemic in the Philippines. Prior to the study, the researchers have noticed that there was an increase in demand for disposable medical masks as a response to the COVID-19 pandemic. The overall objective of the study was to assess the environmental impacts of the life cycle of disposable medical masks in the context of three variables which are energy consumption, waste production, and pollution. The impacts were assessed using related literature and gathered data from respective respondents through the dissemination of online questionnaires among 5 different focus groups. The results from the surveys have shown that the production of healthcare waste has doubled in the past year and is mainly composed of disposable medical masks. In addition, answers from the surveys have shown that the majority of households improperly dispose of their masks by not complying with the set guidelines of the Department of Health. After data collection and discussion, the researchers have observed the connections between the increase in demand for masks and the damaging of the environment in relation to the three variables. To conclude, the researchers have disproved the initial null hypothesis.